Correction: Three bonding modes of bis(2-picolyl)phenylphosphine at iron: isolation of a dinuclear iron complex featuring dearomatized pyridine moieties. Issue 22 (14th June 2015) - Jin, G.; Vendier, L.; Coppel, Y.; Sabo-Etienne, S.; Bontemps, S.
<x xml:space="preserve">Abstract</x> Correction for 'Three bonding modes of bis(2-picolyl)phenylphosphine at iron: isolation of a dinuclear iron complex featuring dearomatized pyridine moieties' by G. Jin et al., Dalton Trans., 2015, 44, 7500–7505.